2009
DOI: 10.1177/0022034509338156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Oral Health Promotion Program in People with Mental Illness

Abstract: More knowledge is needed regarding what works to prevent oral health problems and reduce disparities in oral health. Motivational interviewing (MI) has demonstrated utility for improving health behavior, including among those with severe mental illness. This study tests whether MI enhances the efficacy of an oral health education intervention in individuals with severe mental illness. Sixty individuals were randomly assigned to MI plus oral health education or oral health education alone. Plaque scores, oral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
104
1
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(124 citation statements)
references
References 19 publications
10
104
1
9
Order By: Relevance
“…Two dental hygienists will serve as MI counselors in this study, while in some other studies dental MI was delivered by professional counselors (psychologists or social workers) [39,40]. Delegating the dental counseling work to professional counselors, who require minimal training on health MI, will definitely contribute to an easy implementation of the project.…”
Section: Discussionmentioning
confidence: 99%
“…Two dental hygienists will serve as MI counselors in this study, while in some other studies dental MI was delivered by professional counselors (psychologists or social workers) [39,40]. Delegating the dental counseling work to professional counselors, who require minimal training on health MI, will definitely contribute to an easy implementation of the project.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence with the information provided and the patient's oral hygiene status are then monitored at subsequent treatment sessions 16 Yet, motivating patients to change their oral health behavior is indeed a challenge for dental professionals and a complex issue, which has led to the introduction of Motivational Interviewing (MI) in dentistry . 14,[17][18][19][20][21][22][23][24] MI is a client centered therapeutic method in which the therapist has an important role in increasing the client's readiness for behavior change and reinforcing his/her commitment to change. 25 MI was originally developed for use in the field of drug abuse but has shown to be applicable to initiate beneficial health behavior change within other areas.…”
Section: Health Education Interventionsmentioning
confidence: 99%
“…27 Commonly, MI was used in combination with conventional oral health educational intervention Almomani et al reported a positive effect of a brief MI session, as a prelude to oral health education, on oral hygiene behavior in a group with severe mental illness. 21 Jonsson et al used techniques from the MI method as an integrated part of an individually tailored oral health education program directed to patients receiving periodontal treatment. The intervention comprised seven separate components for tailoring the program to each individual's needs; analysis of knowledge, expectations and motivation, practice of manual dexterity for oral hygiene aids, individual goals for oral hygiene behavior, continuous self-monitoring, generalization of behavior and, finally, maintenance of oral hygiene behavior and prevention of relapse.…”
Section: Health Education Interventionsmentioning
confidence: 99%
“…Furthermore MI has been shown to be effective for enhancing short-term oral health behavior change for people with severe mental illness. (Almomani, Williams, Catley, & Brown, 2009) 3.1 Barriers to oral health care for people with psychiatric disorders Most oral health professionals have limited experiences in providing care for people with psychiatric disorders. (Waldman, Perlman, Waldman, & Perlman, 2002) The barriers exist in organization and financing of the care needed as well as in proposing strategies to enhance the delivery of appropriate treatment.…”
Section: Oral Health Care For People With Psychiatric Disordersmentioning
confidence: 99%